1992
DOI: 10.1037/0735-7044.106.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Selective corticosteroid antagonists modulate specific aspects of spatial orientation learning.

Abstract: Receptors for mineralocorticoids (MRs) and glucocorticoids (GRs) display a high concentration and distinct distribution in the hippocampus. The effects of corticosteroids on behavior mediated by central MRs and GRs were assessed in rats. Spatial navigation is considered to be a sensitive measure for hippocampal functioning. Removal of circulating corticosteroids (via adrenalectomy) impaired spatial learning. In intact rats, blockade of central MRs and GRs by intracerebroventricular injection of selective MR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
372
3
5

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(414 citation statements)
references
References 38 publications
34
372
3
5
Order By: Relevance
“…The domains of cognitive function that are impaired after blockade of MR in men appear to be remarkably similar to those described in animal studies. In animals, spironolactone impaired interpretation of novel information and processes of evaluation and response selection (Oitzl and de Kloet, 1992;Sandi and Rose, 1994). Furthermore, mutant mice with an inactivated MR gene in the forebrain showed impaired learning and working memory owing to behavioral perseverance and stereotypy (Berger et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The domains of cognitive function that are impaired after blockade of MR in men appear to be remarkably similar to those described in animal studies. In animals, spironolactone impaired interpretation of novel information and processes of evaluation and response selection (Oitzl and de Kloet, 1992;Sandi and Rose, 1994). Furthermore, mutant mice with an inactivated MR gene in the forebrain showed impaired learning and working memory owing to behavioral perseverance and stereotypy (Berger et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to cognitive function, animal studies have demonstrated that MR are involved in interpretation of novel information (Berger et al, 2006;Oitzl and de Kloet, 1992;Sandi and Rose, 1994), memory retrieval (Conrad et al, 1997;Yau et al, 1995), and visuospatial learning (Douma et al, 1998;Yau et al, 1999;Yau et al, 1995). In healthy humans, only one study examined the interaction of sleep and MR blockade on consolidation of declarative memory and failed to find an effect of MR blockade (Plihal and Born, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Comparable stressors which were presented unrelated to a learning paradigm were indeed found to suppress memory Corticosteroid actions in the hippocampus 665 formation (85). Paradoxically, GR activation within the context of a learning situation is essential for consolidation of learned information (86,87). Under such conditions, MR activation was found to mediate behavioural reactivity towards the novel situation (88).…”
Section: Physiologymentioning
confidence: 99%
“…This phenomenon could help to explain that in intact rats, spatial learning is exceptionally sensitive to the manipulation of central adrenal steroid receptors (Oitzl, 1998). Thus, for spatial learning, MR activation was related to the strategies adopted during the test, while GR activation was associated with the consolidation of learning (Oitzl and de Kloet, 1992;Oitzl et al, 2001). However, increased and sustained levels of glucocorticoids when administered out of the context of the learning task may interfere with the acquisition or retrieval, thus extinguishing a learned response (Lupien and McEwen, 1997;de Kloet et al, 1999;de Quervain et al, 2000).…”
Section: Introductionmentioning
confidence: 99%